Detailed Case Studies - a Closer Look at Cost Effective Energy and Carbon Emission Optimization in Europe. (November 2015) - Höfler, Karl; Venus, David
Abstract: Renovating the European building stock shows high potential for energy and greenhouse gas reductions. Thereby the optimum balance between energy conservation or efficiency measures and renewable energy generation on-site has to be found, regarding the primary energy and carbon emissions reductions as well as the renovation costs. The whole life cycle of the building has to be considered and therefore Life Cycle Cost (LCC) calculations and Life Cycle Assessment (LCA) are of importance. This paper shows some results to these issues and was prepared within the frame of the IEA EBC Annex 56 research project[1] .